2023
DOI: 10.3390/ijms24076827
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoids, CBDA and THCA, Rescue Memory Deficits and Reduce Amyloid-Beta and Tau Pathology in an Alzheimer’s Disease-like Mouse Model

Abstract: Most studies related to hemp are focused on Cannabidiol (CBD) and Tetrahydrocannabinol (THC); however, up to 120 types of phytocannabinoids are present in hemp. Hemp leaves contain large amounts of Cannabidiolic acid (CBDA) and Tetrahydrocannabinolic acid (THCA), which are acidic variants of CBD and THC and account for the largest proportion of CBDA. In recent studies, CBDA exhibited anti-hyperalgesia and anti-inflammatory effects. THCA also showed anti-inflammatory and neuroprotective effects that may be bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Previous research showed that NMDAR antagonism can induce immobility in the FST (Langen et al, 2012), and our study corroborates the findings that compounds such as CBD and HU-580 can significantly reduce immobility behaviour (Dlugosz et al, 2023;Sales et al, 2019Sales et al, , 2020. Moreover, CBD (Felipe et al, 2013;Leweke et al, 2021;Osborne et al, 2017) and CBDA (Kim et al, 2023) improve or rescue cognitive performance in psychiatric and neurological disorders. Regarding behavioural amelioration, conclusions about receptor correlates seem to be complex.…”
Section: Behavioural Effects Of Hu-580supporting
confidence: 91%
“…Previous research showed that NMDAR antagonism can induce immobility in the FST (Langen et al, 2012), and our study corroborates the findings that compounds such as CBD and HU-580 can significantly reduce immobility behaviour (Dlugosz et al, 2023;Sales et al, 2019Sales et al, , 2020. Moreover, CBD (Felipe et al, 2013;Leweke et al, 2021;Osborne et al, 2017) and CBDA (Kim et al, 2023) improve or rescue cognitive performance in psychiatric and neurological disorders. Regarding behavioural amelioration, conclusions about receptor correlates seem to be complex.…”
Section: Behavioural Effects Of Hu-580supporting
confidence: 91%
“…Among these various uses, therapeutic use was presented by a cultural index value of 40 %. The plant's therapeutic properties that have been experimentally demonstrated by several studies carried out in vitro and in vivo (Haddou et al 2023, Kim et al 2023, Breijyeh et al 2021. Our survey reported 11 diseases 2 c treated by cannabis.…”
Section: Discussionmentioning
confidence: 58%
“…(Mannucci et al, 2017). Research, Society andDevelopment, v. 13, n. 2, e6513245006, 2024 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v13i2.45006 In a recent in vivo study, using rats as models, Kim et al (2023) raises that, in addition to decreasing levels of βA and TAU protein in primary neurons and hippocampus, treatment with CBD and THC decreases cell death and modulates calcium levels. In patients with AD, elevated calcium concentration interferes with signaling pathways, resulting in impaired learning and memory.…”
Section: Therapeutic Benefits Of Cannabidiol In the Context Of The Tr...mentioning
confidence: 99%